Does Li-ion transport occur rapidly in localized high-concentration electrolytes?. Issue 4 (9th January 2023) - Watanabe, Yoshifumi; Ugata, Yosuke; Ueno, Kazuhide; Watanabe, Masayoshi; Dokko, Kaoru
Abstract : Dilution of a highly concentrated Li-salt/sulfolane electrolyte with a non-coordinating hydrofluoroether (HFE) solvent increases ionic conductivity and diffusivity but decreases the Li + transference number. Abstract : The ionic conductivity and lithium-ion transference number of electrolytes significantly influence the rate capability of Li-ion batteries. Highly concentrated Li-salt/sulfolane (SL) electrolytes exhibit elevated Li + transference numbers due to lithium-ion hopping via a ligand exchange mechanism within their –Li + –SL–Li + – network. However, highly concentrated electrolytes (HCEs) are extremely viscous and have an ionic conductivity that is one order of magnitude less than that of conventional electrolytes. Dilution of HCEs with a non-coordinating hydrofluoroether (HFE) lowers the viscosity and produces localized high-concentration electrolytes (LHCE). However, the mechanism of Li + transport in LHCEs is unclear. This study investigated the transport properties of LHCEs prepared by diluting a SL-based HCE with 1, 1, 2, 2-tetrafluoroethyl-2, 2, 3, 3-tetrafluoropropyl ether. Electrolyte viscosity decreases dramatically upon dilution, whereas ionic conductivity increases only slightly. Ion diffusivity increases with increasing HFE content due to the decrease in electrolyte viscosity. However, the Li + transference number declines, because the HFE interferes with conduction via the Li + hopping mechanism. The resulting decrease in the product of ionic conductivity and Li + transference number indicates superior lithium-ion transport in the parent HCE compared with LHCEs.